Efficacy, immunogenicity, and safety of pneumococcal conjugate vaccine in children: a systematic review and meta-analysis - Dai, Qin; Dong, Yujie; Wu, Jing; Peng, Qiyan (Frontiers in Pediatrics, 2025)
PurposePneumococcal infections are the leading cause of childhood morbidity and mortality, and efforts have been made to search for effective means of prevention and control to reduce their serious threat to children's health. This study intends to investigate the efficacy, immunogenicity, and safety of pneumococcal conjugate vaccine (PCV) in children.MethodsA search was conducted in PubMed, Web of Science, Cochrane Library, and Embase up to June 19, 2024. Children aged 0–2 years were included, and PCV was given in the intervention group and a placebo in the control group. The outcomes were immunogenicity, safety, and adverse events. Meta-analyses were conducted using RevMan and Stata17, and the Cochrane Risk of Bias 2.0 was utilized for quality assessment.ResultsEleven studies involving 147,274 participants were included. Meta-analyses revealed that compared with placebo, PCV greatly lowered the incidence of pneumonia (RR 0.78, 95% CI 0.70, 0.87; P < 0.001). PCV also significantly raised the levels of IgG antibody 6B (GMR 22.16, 95% CI 3.73, 131.47; P < 0.001), 9V (GMR 15.18, 95% CI 1.48, 155.27; P = 0.02), 14 (GMR 12.50, 95% CI 1.76, 88.98; P = 0.01), 18C (GMR 20.20, 95% CI 1.47, 276.72; P = 0.04), 19F (GMR 15.43, 95% CI 1.14, 209.15; P = 0.04), and 23F (GMR 13.74, 95% CI 2.42, 78.01; P = 0.003). However, PCV produced no statistically significant increase in the levels of IgG antibody 1/4/5.ConclusionPCV reduces the incidence of pneumonia and improves the levels of IgG antibodies. However, given the lack of data on adverse events in the included studies, we hope that standardized reporting methods for safety outcomes can be adopted in future randomized controlled trials to improve data comparability and utility and provide a more solid basis for evidence-based decision-making.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024570854, PROSPERO CRD42024570854.